HUBUNGAN ANTARA EFEKTIVITAS KEPEMIMPINAN KEPALA SEKOLAH DAN IKLIM ORGANISASI DENGAN PRODUKTIVITAS KERJA GURU SEKOLAH DASAR NEGERI DI KECAMATAN TENGGARONG - M Azhari (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2019)
The research purposes are to find out the relationship between effectiveness principals leadership with teachers work productivity, the relationship between organisational climate with teachers work productivity, the relationship between effectiveness principals leadership and organisational climate simultaneously with teacher’s work productivity. The population of this research were teachers of elementary school in Tenggarong District, with the total of 750 teachers and 88 of them were taken as sample by using random sampling. Quantitative research method is the kind of descriptive research with correlative study. The result of descriptive analysis showed that there has constribution teachers work productivity was in middle category, is equal to 60%, the majority of effectiveness principals leadership in middle category that is equal to 56%, and the organisational climate is in the middle category. So majority that is equal to 62%. Thus a good descriptive performance, motivation and discipline of teachers working at the medium category. The results found that (a) there was a positive and significant relationship between effectiveness principals leadership (X1) with teacher’s work productivity (Y) at a weak level, amounting to 0.356 with a 0.114 coefficient of determination, and the regression equation Ŷ = 37.438 +0.56 X1. (b) there was a positive and significant relationship of organizational climate (X2) teacher’s work productivity (Y) at the current level of closeness, amounting to 0.491 with a coefficient of determination value of 0.2411, and the regression equation Y = 9.082 + 1199X2 (c) there was a positive and highly significant correlation between the variables of work motivation of teachers (X1) and the variable of work discipline teachers (X2) together with special-ed teacher performance variables Samarinda (Y) at the level of closeness that is, that is equal to 0.646 with value coefficient of determination of 0.418 and regression equation y = 11 460 + 0.152X1 + 1.317X2.